Comparison of outcomes of twins conceived spontaneously and by artificial reproductive therapy. (March 2014) - Anbazhagan, Akila; Hunter, Alyson; Breathnach, Fionnuala M.; Mcauliffe, Fionnuala M.; Geary, Michael P.; Daly, Sean; Higgins, John R.; Morrison, John J.; Burke, Gerard; Higgins, Shane; Dicker, Patrick; Tully, Elizabeth; et al.
Abstract Objective: To compare the outcomes of twin pregnancies conceived by artificial reproductive techniques (ART) with those of spontaneous conception. Study design: In this multicenter prospective trial, comparisons were made between methods of conception in twin pregnancies, for maternal and perinatal outcomes. Results: Of 1001 twin pairs, 763/1001 (72.7%) were spontaneously conceived and 238/1001(27.3%) were conceived by ART. There were no significant differences between the two groups with respect to obstetric complications. There were 13 per 1000 (20/1504; 1%) perinatal deaths in the spontaneously conceived group and 6 per 1000 (3/466; 0.6%) in the ART group (p = 0.8141). We found no differences in gestational age at delivery (median 36.9 versus 37.0 weeks), birth weight (median 2520 g versus 2538 g), or in a composite measure of adverse perinatal outcome (17% versus 15%) between the groups. Conclusion: There were no differences in the rate of adverse obstetric or perinatal outcomes between twins conceived naturally compared with twins conceived by assisted conception.